Performance fueling and hydration to maximize training effect - Burks, K. (2015 World Rowing Coaches Conference, 19-22 Nov 2015, Florida, USA, 2015)
The objectives of this presentation are to explain - the Role of carbohydrates as fuel - pre/during, - the role of protein in repair - post, - the role of fluids with thermoregulation, - the impact of recovery on performance in sports and especially in rowing.